2017
DOI: 10.1177/1461444817737296
|View full text |Cite
|
Sign up to set email alerts
|

What did we do when the Internet wasn’t around? Variation in free-time activities among three young-adult cohorts from 1990/1991, 2000/2001, and 2010/2011

Abstract: Comparing the daily time use of three consecutive cohorts of Swedish young adults 20–29 years old, we analyse changes in free-time activity patterns over a period when private Information and Communications Technology (ICT) use was introduced, expanded, and went online. We use Swedish Time Use Survey (TUS) data from 1990/1991, 2000/2001 and 2010/2011 and apply covariate analysis, controlling for important socio-economic factors. Our theoretical approach complements a regular displacement/enhancement perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 36 publications
6
30
0
2
Order By: Relevance
“…In line with findings of TV screen-time being functionally displaced by digital screen-time (Gershuny 2003;De Waal and Schoenbach 2010;Vilhelmson et al 2018), TV screentime decreased between cohorts, while digital screen-time increased. This increase in digital screen-time is consistent with previous research, which has found moderate but consistent increases in digital screen-time between child cohorts since the 1990s (Vilhelmson et al 2018;Goode et al 2019;Fomby et al 2019). Although there were modest increases to engagement in socializing and personal development activities, the far greatest change in child digital activity usage comes with media/leisure activities (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In line with findings of TV screen-time being functionally displaced by digital screen-time (Gershuny 2003;De Waal and Schoenbach 2010;Vilhelmson et al 2018), TV screentime decreased between cohorts, while digital screen-time increased. This increase in digital screen-time is consistent with previous research, which has found moderate but consistent increases in digital screen-time between child cohorts since the 1990s (Vilhelmson et al 2018;Goode et al 2019;Fomby et al 2019). Although there were modest increases to engagement in socializing and personal development activities, the far greatest change in child digital activity usage comes with media/leisure activities (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Early studies were important first glimpses of how emerging digital technologies can affect child wellbeing outcomes. Yet, these studies were conducted at a time in which children's digital and online engagement was 'generally still marginal and impacts were more difficult to discern' (Vilhelmson et al 2018(Vilhelmson et al : 2901, leading to limited samples and highly biased findings (George et al 2018). As access to digital technologies has widened dramatically and an ever-increasing majority of children found their way online, new research in this field has appeared.…”
Section: Impacts Of Children Digital Use On Socioemotional Well-beingmentioning
confidence: 99%
“…A recent study comparing the daily time use of Swedish young adults (20-29 years old) since 1990s showed a considerable increase in ICT use and at the same time period (1990-2011) a consistent decline in offline social activities such as visiting and meeting at home or in public spaces. Young adults performed more free-time activities alone (Vilhelmson et al 2018). Another time use study compared young (15-24 years old) heavy, medium, and light digital media users and their time use patters.…”
Section: Introductionmentioning
confidence: 99%
“…Истраживање спроведено међу шведском омладином показује да се време проведено на интернету повећава, на уштрб времена проведеног у друштвеним активностима, читању књига и новина(Vilhelmson et al, 2018).…”
unclassified
“…A survey conducted among Swedish youth shows that time spent on the Internet has been increasing, at the expense of time spent in social activities, reading books and newspapers(Vilhelmson et al, 2018).…”
mentioning
confidence: 99%